A methodology for evaluating web-based educational systems using statistical multidimensional analysis. (1st January 2011) - Zardas, George; Moschidis, Odysseas; Mavridis, Ioannis; Manitsaris, Athanasios
Current research on web-based learning systems focuses on providing adaptation as part of usability and learnability aspects of these systems. Working in this direction, the (asynchronous adaptive learning and evaluation system) has been developed, which provides new opportunities to the transfer of knowledge between educators and learners by widely incorporating pedagogical principles in order to enhance the effectiveness of the learning procedure. This paper aims to provide an approach on evaluating the impact of adaptivity, usability and learnability based on Nielsen's ten usability heuristics (Nielsen, 1993b) on improving the effectiveness of users' learning in web-based courses. For this purpose, a new evaluation methodology is presented that utilises the statistical method of multidimensional analysis (correspondence analysis) and uses special contingency tables that came from a new coding of scales evaluation. To demonstrate the applicability and effectiveness of the proposals, the evaluation methodology is implemented to the web-based educational system AS.A.L.E.S., resulting in highlighting the characteristics of the AS.A.L.E.S. system that need to be improved.